Social Trust and Anti-immigrant Attitudes in Europe: A Longitudinal Multi-Level Analysis - Mitchell, Jeffrey (Frontiers in Sociology, 2021)
Research investigating how social conditions influence attitudes about immigrants has focused primarily on demographic and economic factors as potential threat inducing contexts that lead to anti-immigrant sentiment. However, the empirical evidence supporting this link is mixed, while social cohesion indicators such as the influence of social trust, has largely been left unexamined. This article uses the European Social Survey (2002-2016) to test how differences in social trust, both within and between countries influence attitudes about immigrants. Results from longitudinal analysis show that countries with higher levels of social trust have more favorable attitudes towards immigrants, and while changes in social trust over time are small, they result in comparably large changes in anti-immigrant attitudes, even when controlling for social factors.